Placing spline knots in neural networks using splines as activation functions. - Hlavácková, Katerina (Neurocomputing :an international journal.)
When using feed-forward neural networks with spline activation functions, the quality of approximation depends on the knot placement of spline functions. We demonstrate a method of choosing equidistant knots in each subdivision of the space when an arbitrary initial division is given, in order to keep the approximation error under a predefined limit.